2014
DOI: 10.1371/journal.pgen.1004113
|View full text |Cite
|
Sign up to set email alerts
|

Serine- and Threonine/Valine-Dependent Activation of PDK and Tor Orthologs Converge on Sch9 to Promote Aging

Abstract: Dietary restriction extends longevity in organisms ranging from bacteria to mice and protects primates from a variety of diseases, but the contribution of each dietary component to aging is poorly understood. Here we demonstrate that glucose and specific amino acids promote stress sensitization and aging through the differential activation of the Ras/cAMP/PKA, PKH1/2 and Tor/S6K pathways. Whereas glucose sensitized cells through a Ras-dependent mechanism, threonine and valine promoted cellular sensitization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 84 publications
(89 reference statements)
2
64
0
1
Order By: Relevance
“…Thus, we further explored the individual role of each amino acid on the high-protein toxicity and we found that the over-representation of methionine (Met), serine (Ser), threonine (Thr) and phenylalanine (Phe) were especially harmful. These amino acids when in excess decrease growth and/or lifespan in a wide variety of life forms such as unicellular algae (Met, Thr and Ser [45]), yeasts (Met, Thr and Ser [46][47][48]), roundworms (Phe [49]), flies (Met [50,51]), rodents (Met, Thr, Ser and Phe [46,[52][53][54]), and even cancer tumour cells (Met and Phe [55]) and other human cells (Met [46]). Methionine is proposed to be related to oxidative stress processes [56].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we further explored the individual role of each amino acid on the high-protein toxicity and we found that the over-representation of methionine (Met), serine (Ser), threonine (Thr) and phenylalanine (Phe) were especially harmful. These amino acids when in excess decrease growth and/or lifespan in a wide variety of life forms such as unicellular algae (Met, Thr and Ser [45]), yeasts (Met, Thr and Ser [46][47][48]), roundworms (Phe [49]), flies (Met [50,51]), rodents (Met, Thr, Ser and Phe [46,[52][53][54]), and even cancer tumour cells (Met and Phe [55]) and other human cells (Met [46]). Methionine is proposed to be related to oxidative stress processes [56].…”
Section: Discussionmentioning
confidence: 99%
“…Both glucose and AA restriction are sufficient to extend the yeast lifespan [13, 14]. AA scarcity drives the accumulation of uncharged tRNAs resulting in activation of general control nonderepressible 2 (GCN2), a protein kinase and important regulator of the general AA control pathway, leading to slow growth [14].…”
Section: Amino Acid Signaling Aging and Dna Damage In Yeastmentioning
confidence: 99%
“…However, a screen for the ability of each AA to sensitize cells to oxidative stress, a phenotype consistently correlated with reduced longevity, three amino acids previously not associated with aging were shown to have the most potent effect on cellular protection, DNA damage and lifespan [18]. When cells were sensitized to oxidative stress by glucose in a Ras-dependent manner, AAs serine (Ser), threonine (Thr) and valine (Val) were the only three that caused a strong sensitization of cells to oxidative stress and promoted aging [13]. In particular, serine activated the Pkh1/2 (PDK1/2 orthologs) while threonine and valine activated TOR signaling, both of which converged to activate the S6 kinase (S6K) ortholog, Sch9 (Fig.…”
Section: Amino Acid Signaling Aging and Dna Damage In Yeastmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also the case for their cell cycle arrest defects: Similar gene deletion phenotypes were observed in the cell cycle dynamics triggered by both nitrogen and carbon starvation. This is relevant in the context that dietary restriction responses depend on nutrient composition (Wu, Liu & Huang, 2013) and that different sensing pathways underlie longevity by glucose or amino acid restriction (Mirisola et al., 2014). But the fact that several protocols of dietary restriction result in lifespan extension, including restriction of glucose, reduced nitrogen levels, and restriction of specific amino acids suggests that the underlying response involves overlapping mechanisms (Kennedy, Steffen & Kaeberlein, 2007).…”
Section: Discussionmentioning
confidence: 99%